Mutated Desmoglein‐2 Proteins are Incorporated into Desmosomes and Exhibit Dominant‐Negative Effects in Arrhythmogenic Right Ventricular Cardiomyopathy. Issue 5 (11th March 2013) - Rasmussen, Torsten B.; Palmfeldt, Johan; Nissen, Peter H.; Magnoni, Raffaela; Dalager, Søren; Jensen, Uffe B.; Kim, Won Y.; Heickendorff, Lene; Mølgaard, Henning; Jensen, Henrik K.; Baandrup, Ulrik T.; Bross, Peter; et al.
<x xml:space="preserve">Abstract</x> Arrhythmogenic right ventricular cardiomyopathy (ARVC) is associated with mutations in the DSG2 gene encoding desmoglein‐2, which makes part of desmosomal junctions providing intercellular adhesion between myocardial and epidermal cells. This study investigated expression of desmoglein‐2 in keratinocytes and myocardial tissue from ARVC patients and demonstrated that carries of DSG2 mutations express and incorporate mutated desmoglein‐2 proteins in myocardial‐ and epidermal desmosomes. These findings in a patient‐specific cell model suggest a dominant‐negative effect of three frequent DSG2 mutations associated with ARVC. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>